49=12y-1

Simple and best practice solution for 49=12y-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 49=12y-1 equation:


Simplifying
49 = 12y + -1

Reorder the terms:
49 = -1 + 12y

Solving
49 = -1 + 12y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-12y' to each side of the equation.
49 + -12y = -1 + 12y + -12y

Combine like terms: 12y + -12y = 0
49 + -12y = -1 + 0
49 + -12y = -1

Add '-49' to each side of the equation.
49 + -49 + -12y = -1 + -49

Combine like terms: 49 + -49 = 0
0 + -12y = -1 + -49
-12y = -1 + -49

Combine like terms: -1 + -49 = -50
-12y = -50

Divide each side by '-12'.
y = 4.166666667

Simplifying
y = 4.166666667

See similar equations:

| 6x+5=-4+2x+17 | | log(3x-3)=log(x+1)+log(4) | | y-1.6=9 | | (2x+3)-(y+3)= | | 4x-(0.56x-1.33)= | | 5=-3x-29 | | 31=a-57 | | 11x-6-6x=6x-4 | | 4-7sinex=0 | | t-8=26 | | z+16=17 | | 4-7sinx=0 | | 2t-1/1-4t^2 | | 6x+2=6(3)+2 | | b+44=52 | | 4.5=1.2timesw | | 9x+2=-3+4x | | 15w^2+31w-28=0 | | 0.05x-0.03y=9 | | 6b=52 | | 7m-25=24 | | 11n+5=137 | | 51-6x=21 | | p/2=6 | | -2x-5y=20 | | 14x+6=2(5x+3) | | 2.5x+48.9=15.0-8.8x | | 2(5x-2)-x=40 | | 17x-12y=-36 | | 3xy/9x | | (m-1)x^2-2(m+1)x+m+4=0 | | 2x+1y=-10 |

Equations solver categories